حفظ القرآن وعلاقته بترقية مهارة الكلام بالمدرسة الثانوية Sains Plus تحفيظ القرآن العمار ميدان سينيمباه سومطرة الشمالية - Febrianti Dewi, Febrianti (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
According to Abdul Al-Da'im Al-Kahil, one of the virtues of the Qur’an is that it helps people improve their Arabic language skills by reading repeatedly, memorizing and listening a lot. This theory supports researchers to discuss further the problem formulation in the eleventh grade of Sains Plus Tahfidzul Qur'an Al-Ammar School where they memorize the Qur’an and study Arabic with the aim of communication at the same time. The questions from this research are: Is there a relationship between memorization of the Holy Qur’an and the speaking skill of eleventh-grade secondary school students at Sains Plus Tahfidzul Qur’an Al-Ammar School. The aim of writing this research is to find out the relationship between memorizing the Holy Qur’an and the speaking skill of eleventh grade secondary school students at the Sains Plus Tahfidzul Qur’an Al-Ammar School. The method used is a quantitative method with a relational type and the data analysis method is a statistical method using the product moment relationship symbol. The result of the research is that the result of memorizing the Qur’an for students in the eleventh grade of secondary school at Sains Plus Tahfidzul Qur’an Al-Ammar School is 51.26, which is in a moderate degree. The result is the speaking skill of students in the eleventh grade of secondary school at Sains Plus Tahfidzul Qur’an Al-Ammar School is 77.87, which is at a moderate level. The relationship between them is a strong relationship because the result of the relationship is 0,784 which indicates that the relationship is strong in a positive way.